THE SIGNIFICANCE OF AFFECT AND MUSICAL RHETORIC IN THE INTERPRETATION OF BAROQUE WORKS ON THE BAYAN - Желізко, Андрій (SWorldJournal, 2025)
The article examines the rhetorical and affective foundations of Baroque musical thinking and the possibilities of their application in contemporary bayan performance. It is shown that affect in the Baroque era functions as a constructive principle that